Prevalence of lumbar disc herniation and its associated factors: A cross-sectional study in Gansu. - Zhiwei Chen; Jirong Zhao; Li Wang; Hong Shao; Liangjia Cao; Xueyun He; Zhenghan Yang; Junfei Ma; Qianwen Chen; Peng Jiang; Licun Zhang; Jihong Hu (PLoS ONE)
Background and objective The prevalence rate of LDH and its influencing factors in Gansu is unclear. This study aims to analyze the prevalence of LDH and influencing factors in Gansu. Methods A stratified multi-stage random sampling method was used to obtain representative samples of residents more than 18 years old from <1500m, 1500-3500m, and >3500m altitude sites in Gansu, China, in June 2022 to August 2022. A unified questionnaire was used for the investigation. Results The total number of people surveyed was 4545, with a prevalence rate of 22.77% for LDH. LDH prevalence differed by latitude, city, age, sex, nationality, education, marital status, income, drinking habits, residence duration, physical activity, exercise intensity, health status (including hypertension, diabetes, CHD, chronic infection, and tumors) (all P <0.05). Logistic regression showed higher LDH risk at high (OR = 2.250) and middle latitudes (OR = 2.551), among males (OR = 0.808), ages 35-49 (OR = 1.530) and 50-64 (OR = 1.991), Tibetans (OR = 1.533) and Hui (OR = 0.557), alcohol consumers (OR = 0.696), those with moderate (OR = 0.742) and mild physical activity (OR = 0.840), cadres (OR = 0.46), workers (OR = 1.568), farmers/herdsmen (OR = 1.840), married individuals (OR = 2.239), residents for ≥36 months (OR = 0.618), annual income ≥50,000 yuan (OR = 1.246), central obesity (OR = 1.399), and those with tumors (OR = 3.953), hypertension (unknown, OR = 1.817), diabetes (yes, OR = 0.529, unknown, OR = 0.565), CHD (unknown, OR = 1.404), and osteoporosis (unknown, OR = 1.404). Conclusion The prevalence of LDH was high, varying significantly with latitude, gender, and nationality, indicating potential lifestyle and demographic influences in Gansu.